Analysis of the histomorphologic profile of invasive cutaneous squamous cell carcinoma from 2002 to 2011 in a pathology laboratory in the region of Campos Gerais, Brazil - Fernanda Magri de Souza; Eloina Do Rocio Valenga Baroni; Mário Rodrigues Montemór Netto (Sociedade Brasileira de Dermatologia, 2017)
ABSTRACT Squamous cell carcinoma is the second most common type of malignant skin cancer. It is also quite aggressive. The increasing incidence of the disease can be altered given its connection with sun exposure. The aim of this study was to establish the clinical and histomorphological profile of squamous cell carcinoma in the region of Campos Gerais, State of Paraná, Brazil and analyze and compare the features of the disease found in the literature. We conducted a cross-sectional descriptive study in a pathology laboratory with selected invasive cutaneous squamous cell carcinoma reports issued after excisional biopsy from January 2002 to December 2011. We selected 374 cases of head and neck SCC, mean age 71.53 years, with a predominance of male patients, moderate degree of histological differentiation, Clark level IV, and absence of perineural, neural, or angiolymphatic invasions. Our results differ on some points from those found in the literature.